Trust and Student Adoption of AI-Enhanced Augmented Reality in Daily Life: A PLS-SEM and fsQCA Investigation - Alam, Bad Re; Öörni, Anssi; Mezei, Jozsef; Bilal, Fatima (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Purpose: AI-powered augmented reality (AI-AR) technologies are increasingly used in everyday consumer activities, yet the factors influencing their adoption remain underexplored. This study examines how perceived usefulness, perceived risk, and system interactivity affect users’ intention to use AI-AR daily, and whether trust in AI mediates these relationships. Design/methodology/approach: An integrated research model grounded in the Stimulus–Organism–Response (S-O-R) framework was proposed and tested using survey data from general technology users across multiple countries. PLS-SEM and fsqca were employed to analyze the relationships among the constructions. Findings: The results show that perceived usefulness and system interactivity positively affect the intention to use AI-AR, whereas perceived risk has an adverse effect. Furthermore, trust in AI significantly mediates the impacts of these factors on adoption intention. Originality/value: The study contributes to literature by introducing an S-O-R-based theoretical framework integrating trust and risk into technology acceptance models. The findings provide practical insights for designing AI-AR applications (in domains such as retail, health, and navigation) that foster user trust, emphasize useful interactive features, and address risk concerns to enhance consumer adoption in daily life.